Tratto Di Scientia D'arme. - Agrippa, Camillo (Medieval and Renaissance Texts., 2009)
Camillo Agrippa's Treatise on the Science of Arms was a turning point in the history of fencing. The author -- an engineer by trade and not a professional master of arms -- was able to radically re-imagine teaching the art of fencing. His treatise was a microcosm of 16th-century thought. It examines the art, reduces it to its very principles, and reconstructs it according to a way of thinking that incorporated new concepts of art, science and philosophy. Introduction, glossary, notes, bibliography, 67 illustrations from the 1553 printing. First English translation.